Effect of propeller type swirl generators on the entropy generation and efficiency of heat exchangers - Kurtbas, Irfan; Durmus, Aydin; Eren, Haydar; Turgut, Emre (Elsevier France-Editions Scientifiques Medicales Elsevier, 2007)
In this study, the effects of propeller-type turbulators located in the inner pipe of co-axial heat exchanger were investigated on entropy generation rate (N-s) and exergy loss rate (E*). Propeller-type turbulators have blade angles (theta) of 10 degrees, 20 degrees, and 40 degrees, also at each angle the propellers have diameter (D-b) of 48 mm, 50 mm and 52 mm. These turbulators were mounted in the inner pipe by different distances (L-t). According to the flow observation experiments, maximum decaying distance of swirl flow was found as 30 cm. The experiments were performed with different distances of turbulators. In this system, heat transfer, entropy generation rate and exergy loss rate were investigated. Then, the effects of angle, diameter and number of the blades on the heat transfer, entropy generation rate and exergy loss rate was investigated and compared with each other for different values of the Reynolds number, from 10(4) to 3 x 10(4), and. Prandtl number equal to 0.71. It was seen that Nusselt number and exergy loss rate approximately increased from 95 to 354 and 0.04 to 0.2 depending on blade angle, interturbulator distance and propeller diameter for 10(4) <= Re < 3 x 10(4). Efficiency of the heat exchanger changed at between 0.17 to 0.72 levels. (c) 2006 Elsevier Masson SAS. All rights reserved.
Keywords: heat exchanger; swirl flow; decaying flow; entropy generation; exergy analysis